(untitled) (Al-Academy, 2025)
Designing effective healthcare environments necessitates a nuanced understanding of how architectural elements—particularly color and lighting—affect users’ psychological and physiological well-being. This study investigates the impact of these elements within Al-Majardah General Hospital in Saudi Arabia through open-ended interviews conducted with patients, healthcare staff, and design professionals. The findings indicate that spatial variables—such as chromatic schemes, lighting quality, acoustic and thermal comfort, ergonomic furniture, and access to natural views—play a significant role in shaping users’ emotional states, behavioral responses, and recovery trajectories. Importantly, these effects vary across demographic and functional groups, underscoring the need for inclusive and adaptive design strategies. This research offers evidence-based insights for healthcare designers, administrators, and policymakers seeking to enhance healing environments through informed spatial interventions. Keywords: Color Psychology, Lighting Design, Healthcare Interiors, Patient Experience, Environmental Design, Staff Well-being